Dispersal limitation, speciation, environmental filtering and niche differentiation influence forest tree communities in West Polynesia - Franklin, J.; Keppel, Gunnar; Webb, E.; Seamon, J.; Rey, S.; Steadman, D.; Wiser, S.; Drake, D. (Blackwell Publishing, 2013)
Aim: Regional patterns of forest composition in West Polynesia were analysed to determine the relative importance of dispersal limitation, speciation, environmental filtering and biotic interactions. Location: West Polynesia (Fiji, Tonga, Samoa). Methods: We applied clustering and indicator species analysis to presence/absence data for 397 tree taxa in 338 forest plots to detect groups of plots sharing similar species composition. Patterns of plot composition and co-occurrence of congeneric species were compared between archipelagos for evidence of dispersal limitation, speciation, and environmental filtering versus competitive displacement or niche differentiation across the three archipelagos at the local (plot) and regional scales. Results: Dispersal limitation was evident in the compositional segregation of inland rain forests across the three archipelagos, whereas compositional overlap was widespread for coastal forests, which are composed of species dispersed by water. Within genera, species numbers attenuated from Fiji to Tonga to Samoa, but speciation also contributed to compositional differences in all three island groups. Environmental filtering was suggested by the distinct composition of both secondary and mature inland rain forest versus coastal forest. At the local scale, however, clumping of congeners, which might suggest fine-scale environmental filtering, was observed for only a minority of inland forest genera. Most genera showed either overdispersion, suggesting competitive displacement or niche differentiation, or patterns not significantly different from random.Main conclusions: Well-established biogeographical patterns of dispersal limitation and speciation contribute to West Polynesian tree diversity at the community scale. Environmental filtering and competitive displacement further structure forest communities; the evidence from this study suggests that environmental filtering is more important at a landscape scale, while competitive displacement may be more important at a local scale, although their relative importance varies considerably among taxa.